PEMETAAN POTENSI KAMPUNG KULAKEN BERBASIS DATA SPASIAL DI DISTRIK WALELAGAMA KABUPATEN JAYAWIJAYA, PAPUA PEGUNUNGAN - Sabriani Sabriani; Nur Aisyah Takdir; Andi Astri Faradiba; Yusman Yusman; Marsiana Domanilia Wanimbo (Universitas Negeri Makassar, 2026)
Kulaken Village, located in Walelagama District, Jayawijaya Regency, Papua Highlands, possesses various local resource potentials that have not been optimally documented in digital spatial data form. This condition has created difficulties for the village government in preparing development programs, managing regional potential, and determining priorities for Village Fund Allocation (ADD). This Community Service Program aimed to map the village potentials of Kulaken Village based on spatial data to support more targeted and data-driven village development planning. The method applied was participatory mapping using a Geographic Information System (GIS) approach with ArcGIS software. The implementation stages included mapping deliberation, field surveys, spatial data collection, data processing, verification, and preparation of digital village potential maps. The results revealed several main potentials in Kulaken Village, including beekeeping, pig farming, goat farming, cattle farming, and red fruit agriculture. These potentials were successfully mapped into digital spatial-based maps that systematically and informatively illustrate the distribution of village resources. The application of GIS in this activity facilitated easier and more accurate access to regional potential information for both the community and village officials. Furthermore, the mapping results can serve as a basis for development policy-making, local economic development, and the preparation of sustainable digital village blueprint data.